The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1111/ctr.12212
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral treatment for hepatitis B virus recurrence following liver transplantation

Abstract: The purpose of this study was to identify the factors associated with the recurrence of hepatitis B virus (HBV) following liver transplantation (LT) for HBV-related disease and to recognize the outcome of treatment for HBV recurrence with oral nucleos(t)ide analogues. Six hundred and sixty-seven LTs were performed for HBsAg-positive adult patients in our institute from 1996 to 2010. HBV prophylaxis was performed by hepatitis B immunoglobulin (HBIG) monotherapy or HBIG and entecavir combination therapy. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…In the setting of HBV recurrence, the first-line salvage antiviral regimens always are LAM plus ADV or ETV monotherapy in our center, which is similar to other center in Asia [8]. In fact, LAM-related mutation was detectable in majority of recipients when HBV recurrence was diagnosed, which could significantly reduce the efficacy of ETV.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…In the setting of HBV recurrence, the first-line salvage antiviral regimens always are LAM plus ADV or ETV monotherapy in our center, which is similar to other center in Asia [8]. In fact, LAM-related mutation was detectable in majority of recipients when HBV recurrence was diagnosed, which could significantly reduce the efficacy of ETV.…”
mentioning
confidence: 61%
“…Although HBIG combined with NUCs (mainly LAM) after LT has been the most effective prophylaxis regimen for HBV recurrence in clinical practice until now, HBV recurrence was associated with graft loss, HCC recurrence, and significantly decreased survival rate in LT recipients [8,9]. Furthermore, recent studies have found that high preoperative HBV DNA load (>10 5 copies/ml), HBV mutation, and HCC in the explant liver were independent risk factors for HBV recurrence following LT [10].…”
mentioning
confidence: 99%
“…HBV prophylaxis protocol for LT recipients was combination regimen of high dose HBIG (human HBV-specific hepatitis B immunoglobulin, Greencross, Seoul, Korea) with an oral nucleotide analogue [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…The only study based on a population of LT patients, including more than 1000 cases, came from Korea (n = 1524), while the sample size was above 100 cases in 13 studies. 22,29,33,[35][36][37]49,50,54,57,58,60,62,64 In the remaining 37 studies, the sample size was smaller than 100 cases.…”
Section: Review Of the Eligible Studiesmentioning
confidence: 99%